Analisis Willingness to Pay Masyarakat terhadap Mata Air Aek Arnga di Desa Sibanggor Tonga, Kecamatan Puncak Sorik Marapi, Kabupaten Mandailing Natal - Siti Maryam Nasution; Agus Purwoko; Kansih Sri Hartini (Program studi Kehutanan USU, 2015)
Water is an important element in human life. Water is used for various purposes including for drinking, domestic using, and all human activities. The purpose of research was to analyze the economic value of Aek Arnga spring and the factors that affect the value of the willingness to pay (WTP) for the payment of environmental services community. The method was used in this research was Contingent Valuation Method (CVM). CVM was a method of survey techniques that asked residents about the value or price of the commodity they accepted to pay that didn’t have market’s value as environmental goods. The factors that effected respondent’s willingness to pay for environmental services in this research was the average household income, the amount of water users, and the amount of water need. WTP’s value obtained from this research was the value that would be given by the respondents for the environmental services that was producted by Aek Arnga spring per liter per household. The average WTP values of respondents was Rp. 109.65/Hh/day while the total value of WTP was Rp. 14,692.83 /day. The value of environmental services of Aek Arnga spring by community was around 9,454,715.45 liters/year. While the potential value of Aek Arnga spring was Rp. 1,036,709,549.09 /year that could be done to restore ecology of the forest area of 9.40 ha.Keywords: Aek Arnga spring, environmental services, willingness to pay, the value of water services